Peningkatan Potensi Wisata Desa Kebontunggul Melalui Pelatihan Produksi Konten Audio Visual di Lembah Mbencirang - Agatha, Alvin Syafril; Kusumo, Dewo Adji Suryo (Unri Conference Series: Community Engagement, 2024)
Kebontunggul Village in Mojokerto Regency has untapped tourism potential, notably Lembah Mbencirang. This community service aims to train village residents, particularly the Village-Owned Enterprises (Bumdes), in producing audiovisual content to promote this tourism potential. The methods used include training in the theory and practice of audiovisual content production, focusing on the use of mirrorless cameras and stabilizers. The training covers the stages of pre-production, production, and post-production. Participants are trained to produce high-quality and professional videos through direct field practice at Lembah Mbencirang. The outcome of this activity is the creation of several promotional videos for the village’s tourism, especially Lembah Mbencirang, produced by participants using mirrorless cameras and stabilizers. This content is published through social media to enhance the visibility of Kebontunggul Village's tourism potential. This activity is expected to improve the villagers' abilities to produce high- quality audiovisual content independently and sustainably, thereby supporting the development of the village's tourism sector in the future, especially in promoting the beauty of Lembah Mbencirang and other tourist destinations.